Kidz Studios Venture / Amirul Akmal Abu Bakar ... [et al.] - Abu Bakar, Amirul Akmal; Rosdi, Muhammad Ridzwan; Ahya, Muhammad Khairil; Syed Osman, Syed Ahmad Al Haddad; Ab Wahab, Muhammad Azizi (2019)
Case study has been conducted towards KIDZ STUDIOS VENTURE SDN BHD. Thjs company was established on 4th December 2013 and based in Shah Alam, Selangor. The nature-/of the business is in servicing sector which they provide on graphic design and printing. KIDZ STUDIOS VENTURE (KSV) is running through direct selling business models to obtain their income. The objective of this study on KIDZ STUDIOS VENTURE (KSV) is to examine their business problem and provide solution outcome which helps on the company development. The company has good reputation towards their customer as they always delivers on customer needs. The company indeed is taking well of their customers as they believed when customer comes first the outcome will last. However, there is problem arise that hinders on the company development which is time management. In doing business, taking care of the time is very important in order for the company to grow. The pompany has problem regarding late goods arrival towards their customer and often receive complains regarding that matters. This problem arise because of the time taken for processing goods prior order received is quite long and somehow could not meet customer expectations.